Clinical characteristics and short-term prognostic factors of spontaneous intracerebral hemorrhage in high⁃altitude plateau - ZHAO Wei⁃wei; JI Shi⁃yong; LIAN Yu⁃qing; ZHUO Ma; ZHAO Yu⁃hua; YUAN Jing (Chinese Journal of Contemporary Neurology and Neurosurgery)
Objective To investigate the clinical characteristics and current treatment status of spontaneous intracerebral hemorrhage (ICH) patients in Xizang Autonomous Region and to screen for factors influencing short⁃term poor neurological prognosis. Methods A total of 200 spontaneous ICH patients admitted to People's Hospital of Xizang Autonomous Region between April 2020 and November 2022 were included. The modified Rankin Scale (mRS) was used to assess short-term neurological prognosis at discharge. Univariate and multivariate Logistic regression analyses were performed to identify influencing factors associated with short⁃term poor neurological prognosis. Results The study included 200 patients with ICH. Their average age of onset was (65.42±7.78) years, with a high prevalence of hypertension (97.50%, 195/200) and basal ganglia hemorrhage (59%, 118/200). The age at onset was older and the mortality rate (2%, 4/200) was lower than previously reported. Based on mRS score at discharge, patients were divided into a good prognosis group (0-2 points, n=72) and a poor prognosis group (3-6 points, n=128). Logistic regression analysis in the 148 patients without intraventricular extension showed that basal ganglia hemorrhage (OR=7.098, 95%CI:3.043-16.557; P=0.000) and hemorrhage volume (per 10 ml increase; OR=1.485, 95%CI:1.240-1.777, P=0.000) were risk factors for short⁃term poor neurological prognosis. Conclusions Spontaneous ICH in Xizang region exhibits unique epidemiological characteristics, with a notably high prevalence of hypertension and basal ganglia hemorrhage, and a delay in the age at onset and a reduction in the mortality rate compared to previous reports. Hemorrhage volume and basal ganglia involvement are critical determinants of short-term poor neurological prognosis. Strengthening hypertension management, optimizing acute⁃phase treatment, and enhancing medical resource allocation are essential to improving prognosis.